O Ensino Médio modular no campo: um estudo na escola Rui Barbosa, Medicilândia, Pará - ARAÚJO, Alcinei da Silva (2021)
The experience in the Supervised Internship carried out in high school motivated the choice on the theme of this research of the Course Conclusion Work (TCC). Therefore, the research was developed from Supervised Internship III, at Tempo Comunidade VII. The objective of this work presents a study about the theme of the Modular Organizational Teaching System (SOME), offered at the Rui Barbosa Municipal Elementary School, located at Agrovila Jorge Bueno da Silva - km 70 lane, 20 km from the seat of the municipality of Medicilândia. This study is guided by the qualitative and quantitative approach, by using elements that contributed to the frame of reference in the context of which the object of study is made explicit, such as the construction of graphics, use of photographs, research data produced over the years. supervised internships, through field research involving community times, data from field notebooks, interviews with students, teachers from the rural modular, school directorate for the internship field, directorate of the headquarters school, coordination of the 10th regional and state education secretary Pará and the municipality of Medicilândia. For the development of this study, it was necessary to identify the historical aspects of that city of Medicilândia and the Transamazônica Highway due to the fact of the relational connections with the history of the Rui Barbosa School and with the community. In this work, there is the exercise of contextualizing high school in the countryside from the history of the Rui Barbosa School, from the mode of offering modular education in the municipality of Medicilândia, mainly due to the demand for quality public education in the countryside, in elementary school to high school, considering that educational issues are thematic of research and concern in the context of the reality of schools in the city and the countryside and their demands projected for governmental actions. The research results revealed that the State needs to create public policies to serve the population of peasant communities, especially in the area of education, invest in the acquisition of books and teaching materials for basic schools, rethink the curriculum, in order to contextualize it with the social practices of the subjects and their temporalities and the main thing, guaranteeing SOME teachers, continuous training, to improve their knowledge, in the search for new teaching methodologies guided by a differentiated, public and quality education in the field.